Improved polygenic prediction by Bayesian multiple regression on summary statistics - Luke R. Lloyd-Jones (Nature Portfolio, 2019)
Various approaches are being used for polygenic prediction including Bayesian multiple regression methods that require access to individual-level genotype data. Here, the authors extend BayesR to utilise GWAS summary statistics (SBayesR) and show that it outperforms other summary statistic-based methods.